A multimethod approach to assessing motor skills in boys and girls with autism spectrum disorder. (July 2021) - Crippa, Alessandro; Craig, Francesco; Busti Ceccarelli, Silvia; Mauri, Maddalena; Grazioli, Silvia; Scionti, Nicoletta; Cremascoli, Alice; Ferrante, Camilla; Visioli, Chiara; Marzocchi, Gian Marco; Molteni, Massimo; Nobile, Maria
Motor abnormalities are highly prevalent in children with autism spectrum disorder and are strongly predictive of adaptive functioning. Despite the documented sex bias in the prevalence of the disorder, the impact of sex differences on motor abnormalities has been overlooked. The goal of this study was to investigate differences in the motor profile of boys and girls with autism spectrum disorder aged 3–11 years using a multimethod approach. Ninety-eight children with autism spectrum disorder and 98 typically developing children were assessed using the Movement Assessment Battery for Children 2, the Developmental Coordination Disorder Questionnaire, and the kinematic analysis of a reach-to-drop task. Results from principal components analysis on reach-to-drop-dependent measures indicated four components, accounting for kinematic parameters of the motor task. Irrespective of sex, children with autism spectrum disorder showed worse scores on Movement Assessment Battery for Children 2 and Developmental Coordination Disorder Questionnaire subscales than typically developing children. Interestingly, a diagnosis-by-sex interaction was found on a kinematic feature measured in the last part of the movement, with girls with autism spectrum disorder presenting altered motor anticipation. Although preliminary, these findings suggested that sex-related nuances in motor functioning of children with autism spectrum disorder could be insufficiently captured by existing motor measures. Lay abstract: Motor peculiarities are often reported in children with autism spectrum disorder and may predict subsequent adaptive functioning and quality of life. Although the sex bias in the prevalence of the disorder is well documented, little is known about differences in motor profile in males and females with autism spectrum disorder. Our goal was to study differences in motor functioning of boys and girls with autism spectrum disorder aged 3–11 years compared with typically developing children. Their motor performances were evaluated using a multimethod approach, including standardized motor tests, caregiver reports, and a detailed motion capture analysis of a simple reach-to-drop movement. We found that, irrespective of sex, children with autism spectrum disorder had worse scores than typically developing children on standardized tests and on caregiver reports. Interestingly, girls with autism spectrum disorder, but not boys, presented altered motor anticipation in reach-to-drop. Our findings emphasize the need for more sex-specific assessment of motor function in autism spectrum disorder.